The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10984-017-9244-y
|View full text |Cite
|
Sign up to set email alerts
|

Elements affecting the development of professional learning communities in schools

Abstract: This article focuses on the development of professional learning communities (PLCs), which are communities within schools, composed of voluntary participating teachers facilitated by school principals with a specific task to accomplish as part of a larger innovation project. Four PLCs were observed during 3 years by using questionnaires and participatory research. The questionnaires revealed that PLCs differed in their group characteristics, collective learning processes and outcomes. Through participatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 49 publications
2
21
0
3
Order By: Relevance
“…This was shared with teachers and teacher leaders at the start of the PLC program. In the academic setting of schools, organisational goals are anchored on teaching and learning to improve student learning outcomes, and these goals are accompanied by core values that shape the culture of the school (Schaap & de Bruijn, 2018). PLC programs reported to have been successfully initiated in schools in Europe and the Asia Pacific region refer back to the school leaders' capabilities to clearly communicate the mission and vision, as well as motivate teachers through a genuine manifestation of collaborative learning (Turner et al, 2018;Wang, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was shared with teachers and teacher leaders at the start of the PLC program. In the academic setting of schools, organisational goals are anchored on teaching and learning to improve student learning outcomes, and these goals are accompanied by core values that shape the culture of the school (Schaap & de Bruijn, 2018). PLC programs reported to have been successfully initiated in schools in Europe and the Asia Pacific region refer back to the school leaders' capabilities to clearly communicate the mission and vision, as well as motivate teachers through a genuine manifestation of collaborative learning (Turner et al, 2018;Wang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary research in the field of education embarks on the continuous examination and exploration of professional learning communities or PLCs (Hairon et al, 2017;Schaap & de Bruijn, 2018). What was initially thought of as a 'trendy initiative' in response to raising standards of teaching and learning has endured the scrutiny of critics and has lived on to be continuously assessed on the merits of its effects on pedagogical and organisational improvement (Gomes, 2013).…”
Section: The Implementation Of Professional Learning Communitiesmentioning
confidence: 99%
“…Successfully constructing PLCs requires balancing the group's objectives with the individual professional objectives and needs of each participant (Little, 2002), members' engagement in the community (Hardman, 2011), and leadership (Hairon, Goh, & Chua, 2015). Common challenges for teachers trying to construct a well-developed PLC include group tensions, reluctance to speak openly for fear of personal or professional backlash, a lack of a shared vision for the group's purpose and operation, and lack of ownership (Dooner, Mandzuk, & Clifton, 2008;Schaap & deBruijn, 2018).…”
Section: Professional Learning Communitiesmentioning
confidence: 99%
“…Affordances and personal features do not cause tensions in themselves, but certain combinations of personal features and affordances cause feelings of conflict or frictions and thus a perceived tension. For example, Schaap and De Bruijn (2018) showed that participating in PLCs inherently includes tensions between professional learning and work pressure, between participation in the PLC and the primary process of teaching, between professional development and school improvement, and between individual and collective learning.…”
Section: Theoretical Frameworkmentioning
confidence: 99%